Luminol luminescence-based theranostics for pre-clinical breast adenocarcinoma - Alshetaiwi, Hamad S. (Kansas State University, 2014)
Breast cancer ranks second as a cause of cancer death in women in the USA. Detection of early tumors and tumor-targeted treatments could decrease the problems associated with breast cancer management. Photodynamic therapy (PDT) is a cancer treatment that uses a photosensitizer and a specific wavelength of light and is currently in clinical trials for breast cancer. When tumor cells which have absorbed photosensitizer are exposed to the correct wavelength of light, reactive oxygen species are generated, resulting in tumor cell death. Poor tissue penetration of light is a major limitation in PDT, restricting its use to treatment of localized tumors. Light generation at the tumor area might increase the effectiveness of PDT. Polymorphonuclear neutrophils (PMNs) are known to often infiltrate breast adenocarcinoma, and their activatation in tumor stroma produces luminescence in the presence of luminol. Here, we hypothesized that luminol can be used as a theranostic agent for luminescence-based early tumor detection (diagnosis) and in situ PDT (treatment). BALB/c mice were transplanted with 4T1 mammary adenocarcinoma cells to establish a breast adenocarcinoma model. The early tumor detection objective was tested by daily intraperitoneal injection of luminol and in vivo luminescence imaging. To test the PDT treatment objective,the photosensitizer 5-aminolevulinic acid (ALA) and luminol were administered to mice through intraperitoneal and intravenous routes, respectively. This treatment regimen was repeated six times and ALA alone/luminol alone/saline treated tumor-bearing mice were used as controls. Results demonstrated that luminol allowed detection of activated PMNs only two days after 4T1 cell transplantation, even though tumors were not yet palpable. Relative differences in the increase of tumor volume and final tumor weights were analyzed to test the in situ PDT. Analysis of the data showed luminol treatments resulted in breast adenocarcinoma tumor growth attenuation. In conclusion this study provides evidence that luminol can be a theranostic agent for breast adenocarcinoma.
Keywords: Cancer therapy; Cancer detection; Breast cancer; Photodynamic therapy; Bioluminescence; Luminol; Medicine (0564)